Sandwich lanthano-silicotungstates: Structure, electrochemistry and photoluminescence properties - Juliao, Diana
Sandwich-type of luminescent silicotungstates were prepared using the inorganic ligand [SiW11O39](8-)(SiW11) coordinating different lanthanide ions (Eu3+, Tb3+, Dy3+): Eu(SiW11)(2), Tb(SiW11)(2) and Dy(SiW11)(2). The potassium salts of these compounds were characterised by several techniques and the crystal structure of Eu(SiW11)(2) was studied. The lanthanide ion in the sandwich structure reveled to have some influence in the electrochemical behaviour of these compounds in aqueous solutions, mainly in the first of the two reduction processes observed for the tungsten atoms. The influence of scan rate on the voltammetric characteristics of the first tungsten reduction process led to the conclusion that the process was diffusion-controlled. The pH of the electrolyte solution showed significant effect on the electrochemical behaviour of these compounds, suggesting that the tungsten reductions processes are accompanied by addition of two to three protons. The photoluminescence properties of Eu(SiW11)(2) and Tb(SiW11)(2) were investigated in some detail, namely as a function of temperature and pressure (with exposure to a high vacuum of ca. 5 x 10(-6) mbar). Both compounds are iso-structural with a single Ln(3+) site and with absence of water molecules coordinated to the lanthanide ions. Contrary to Eu(SiW11)(2), the Tb(SiW11)(2) compound is not optically active at room temperature and shows a very sensitive photoluminescence with the temperature on the range of 11-150 K which was interpreted by the effect of a back energy transfer de-excitation process. (C) 2012 Elsevier Ltd. All rights reserved.